Workshop Penentuan Parameter Spesifik dan Non Spesifik Bahan Baku Obat Tradisional pada Mahasiswa Farmasi UHAMKA Melalui PKKM - agustin yumita; Ni Putu Ermi Hikmawanti; Fujianti; Novia Delita (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2023)
Indonesia's abundant biodiversity provides good opportunities for developing medicines, especially traditional medicines made from plant materials. However, it is necessary to standardize the process to realize quality, safe, and efficacious traditional medicinal preparations. This standardization process is essential. This workshop aims to provide information on the standardization of raw materials for traditional medicines to have the knowledge and ability to standardize medicinal raw materials. At the initial stage, participants will be given a pretest. Furthermore, participants studied specific and non-specific parameters, and at the last stage, the participants were given a posttest. The data obtained from the pretest and posttest will then be processed using Excel and the IBM SPSS Statistics version 25.0 application. From the results of the workshop activities, the average value of the pretest results was 62.5806, smaller than the posttest results of 83.2258. This indicates a significant difference of P < 0.05 between the pretest and posttest. In this workshop, the team provided an understanding to the participants in standardizing the raw materials for traditional medicines. The statistical results also showed a significant effect on the treatment before being given training and after being given training to the workshop participants.